Situasi Diglosia Pada Penutur Bahasa Bali Di Kota Mataram Nusa Tenggara Barat - Wiya Suktiningsih (LPPM Universitas Bumigora Mataram, 2019)
The linguistic situation a group of people is influenced by linguistic aspects and context. This research was conducted to see the Balinese speakers' diglossia, among teens of Balinese and the factors that influence the situation. Ethnic Balinese in the city of Mataram, have the ability to speak Balinese (B1), Sasak (B2) and Indonesian (B3). Teens of Balinese in Mataram have a high mobility, interacting with various speech partners with different backgrounds and domains. That affects the choice of language based on domain factors, participant, speech event and topic. This situation is interesting topic to study using the Sociolinguistic studies. This study identifies the factors that influence the choice of language by Balinese speakers, especially teens of Balinese in a speech event in a particular domain. This research is a qualitative study used the data were collected using the methods and techniques: Survey, interview and observation. The sample used was 30 teens of Balinese aged 18-25 years who lived in the city of Mataram. The findings out the research revealed. First: the language situation of Balinese speakers of Mataram city becomes the background there is a process of language choice B1, B2 or B3. Second: This study conducted observations in four domains: family, friendship, education and vogue. Third: This research finding three main factors as influencing the choice of speakers' language in social interactions : (1) time and place; (2) participans in the interaction, (3) and topic in the speech event.